Safarnāma-yi Gawhar-i maqṣūd - Tihrānī, Āghā Sayyid Muṣṭafā (Miras Maktoob, ISBN: 9789004365452., 2020)
Travel notebooks have existed almost ever since writing was invented. Two travel narratives with high dramatic and literary value from classical antiquity are Homer's Odyssey and Virgil's Aeneid . In Arabic literature, Ibn Baṭṭūṭa's (14th cent.) famous Travels come to mind, and for medieval Persian literature, the travel notebook ( Safar-nāma ) of Nāṣir Khusraw (11th cent.). While the safar-nāma has a long history in the Persianate world, in the 19th and early 20th centuries, it enjoyed a special kind of popularity. Today, more than 250 safar-nāma , for the most part from that period, are preserved in libraries throughout Iran. The travel notebook published here was written in the autumn of 1908, just after Muḥammad ʿAlī Shāh's coup d'état against the constitutional movement of Iran. Its author Āghā Sayyid Muṣṭafā Tihrānī (Mīrkhānī), a politician and supporter of that movement, writes critically about this and many other social issues while traveling from Tehran to Mashhad, unaware that one day, his comments would be published.